Area Search for a Moving Target - Nanda, J.N. (Defence Science Journal, 2013)
When a target has an apriori existence in an area A and a fraction phi of the area is searched, there are well-known expressions for the detection probability when the target is stationary. In this paper the detection probability is worked out for a more important case when the target is in motion. It must be assumed, however, that the target manages to remain in the area in which it has apriori existence by permitting suitable changes in its direction of motion. The detection probability will depend on the ratio of the speeds of the target and the searcher in a complex way. The computation should involve a computer programme but analytical expressions can be approximately derived for phi <<1. The calculated probability is less than phi which is the detection probability for continuous search for a stationary target and more than the value for a random search.